2018
DOI: 10.1016/j.pharep.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the neonatal streptozotocin model of diabetes in rats: Evidence for a model of neuropathic pain

Abstract: Results suggest that nSTZ leads to activation of SGC, microglia and astrocytes in DRG and spinal cord. Pharmacological profile in the nSTZ model resembles diabetic neuropathic pain in humans. Our findings support the conclusion that the nSTZ rat model has utility for the study of a long-lasting diabetic neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Mounting evidence suggests that activation of satellite glial cells indeed participate in neuropathic pain. 39 41 Thus, the transient presence of ATF2 in these cells may have a role in neuropathic pain. Our data partially agree with other observations indicating that stimulation of adult DRG neurons by doxorubicin or ultraviolet irradiation ( in vitro ) and axotomy ( in vivo ) induce a rapid (2–24 h) and consistent (3–20 days) down-regulation of ATF2.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence suggests that activation of satellite glial cells indeed participate in neuropathic pain. 39 41 Thus, the transient presence of ATF2 in these cells may have a role in neuropathic pain. Our data partially agree with other observations indicating that stimulation of adult DRG neurons by doxorubicin or ultraviolet irradiation ( in vitro ) and axotomy ( in vivo ) induce a rapid (2–24 h) and consistent (3–20 days) down-regulation of ATF2.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, streptozotocin-induced experimental diabetes has been produced in neonatal rats (nSTZ) and it was demonstrated that in addition to glucose intolerance, the hyperglycemia induced in these animals was much milder than in adults (21). Also, C-fibre nerve conduction velocity in nSTZ animals was reduced in a similar fashion to adults, but it occurred considerably later in neonates following treatment with streptozotocin.…”
mentioning
confidence: 99%
“…It is noteworthy that all these characteristics were attended by tactile allodynia to von Frey filament application, substantiating the notion that nSTZ causes nerve injury. The nSTZ diabetic model has been designated as one which mimics type 2 diabetes (22), although more recent authors acknowledged that their findings did not fully support this overall postulation (21). Nevertheless, nSTZ did disclose some of the features of type 2 diabetes and the animals in the nSTZ model were much healthier than those in the type 1 diabetic model (STZ in adult animals).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Microglia The role of spinal microglia in neuropathic pain syndromes is complex [137] and, at least for CIPN, is not completely understood. Investigations of the role of microglia in CIPN have presented opposing findings.…”
Section: Immune Cells T-cellsmentioning
confidence: 99%